Translating the Body Medical Education in Southeast Asia - Pols, Hans; Thompson, C. Michelle; Warner, John Harley (National University of Singapore Press, 2017)
Western conceptions of the body differ significantly from indigenous knowledge and explanatory frameworks in Asia. As colonial governments assumed responsibility for health care, conceptions of the human body were translated into local languages and related to vernacular views of health, disease, and healing. The contributors to this volume chart and analyze the organization of western medical education in Southeast Asia, public health education in the region, and the response of practitioners of "traditional medicine". "Translating the body" is a shorthand for the formulation of medical ideas, practices, and epistemologies in contexts that require both interpretation and transmission. The process is both linguistic and cultural, and in approaching medical education, the book follows recent work in translation studies that underscores the translation not merely of words but of cultures.